A Comprehensive Analysis of Echinococcus granulosus Infections in Children and Adolescents: Results of a 7-Year Retrospective Study and Literature Review - Cristina Maria Mihai; Ancuta Lupu; Tatiana Chisnoiu; Adriana Luminita Balasa; Ginel Baciu; Vasile Valeriu Lupu; Violeta Popovici; Felicia Suciu; Florin-Daniel Enache; Simona Claudia Cambrea; Ramona Mihaela Stoicescu (Pathogens)
Cystic echinococcosis (CE) is a neglected tropical parasitic disease linked with significant social and economic burdens worldwide. The scientific community has minimal information on echinococcosis in Romanian people, and hospital medical records are the only sources that may be used to investigate its status. A 7-year retrospective clinical study on pediatric patients with CE from Southeast Romania was performed, and 39 children and adolescents were included, aged 2–15 years old. They were hospitalized with cystic echinococcosis in the Pediatric Department and Pediatric Surgery Department of Constanta County Clinical Emergency Hospital “St. Apostle Andrew” between 1 January 2017 and 1 October 2024. Twenty-nine (74.36%) pediatric patients came from rural zones, and 10 (25.64%) had urban residences. In total, 28 children (71.79%) had contact with four different animals (dogs, goats, pigs, and sheep); only four were from urban zones, and they had contact only with dogs. Data regarding the length of hospital stay, cyst location, and complications were collected and analyzed. According to the medical files, the diagnosis was established using imaging techniques and serological tests for CE. IgE and IgG reported appreciable variations in correlation with all parameters, and significant differences (p < 0.05) were recorded. IgE levels considerably increased in cases of no animal contact, pulmonary involvement, complications, surgical treatment, and multiple hospitalizations. Moderate IgE values were recorded in cases of urban residences, pig and sheep contact, and hepatic involvement. The IgG concentration considerably increased with sheep contact and moderately increased in cases of rural zones, hepatic involvement, complications, and surgical treatment. The results show that incidental discovery, symptoms, complications, multiple dissemination, pulmonary involvement, and dog and pig contact increase the hospitalization time. Extensive data analysis supports our results. Our findings highlight the complexity of managing E. granulosus infections in children and evidence the importance of a multidisciplinary approach, combining early diagnostic tools, tailored medical therapy, and careful surgical intervention when necessary.